Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Disease-associated CTNNBL1 mutation impairs somatic hypermutation by decreasing nuclear AID. - Kuhny, Marcel; Forbes, Lisa R; Çakan, Elif; Vega-Loza, Andrea; Kostiuk, Valentyna; Dinesh, Ravi K; Glauzy, Salomé; Stray-Pedersen, Asbjorg; Pezzi, Ashley E; Hanson, I Celine; Vargas-Hernandez, Alexander; Xu, Mina LuQuing; et al. (J Clin Invest, 2020)
Patients with common variable immunodeficiency associated with autoimmune cytopenia (CVID+AIC) generate few isotype-switched B cells with severely decreased frequencies of somatic hypermutations (SHMs), but their underlying molecular defects remain poorly characterized. We identified a CVID+AIC patient who displays a rare homozygous missense M466V mutation in β-catenin-like protein 1 (CTNNBL1). Because CTNNBL1 binds activation-induced cytidine deaminase (AID) that catalyzes SHM, we tested AID interactions with the CTNNBL1 M466V variant. We found that the M466V mutation interfered with the association of CTNNBL1 with AID, resulting in decreased AID in the nuclei of patient EBV-transformed B cell lines and of CTNNBL1 466V/V Ramos B cells engineered to express only CTNNBL1 M466V using CRISPR/Cas9 technology. As a consequence, the scarce IgG+ memory B cells from the CTNNBL1 466V/V patient showed a low SHM frequency that averaged 6.7 mutations compared with about 18 mutations per clone in healthy-donor counterparts. In addition, CTNNBL1 466V/V Ramos B cells displayed a decreased incidence of SHM that was reduced by half compared with parental WT Ramos B cells, demonstrating that the CTNNBL1 M466V mutation is responsible for defective SHM induction. We conclude that CTNNBL1 plays an important role in regulating AID-dependent antibody diversification in humans.
Keywords: Amino Acid Substitution; Apoptosis Regulatory Proteins; B-Lymphocytes; Cell Line; Child, Preschool; Common Variable Immunodeficiency; Cytidine Deaminase; Female; Homozygote; Humans; Immunologic Memory; Mutation, Missense; Nuclear Proteins; Somatic Hypermutation, Immunoglobulin

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease. - Cook, Sarah A; Comrie, William A; Poli, M Cecilia; Similuk, Morgan; Oler, Andrew J; Faruqi, Aiman J; Kuhns, Douglas B; Yang, Sheng; Vargas-Hernandez, Alexander; Carisey, Alexandre F; Fournier, Benjamin; Anderson, D Eric; et al. (Science, 2020)
Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in , which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulatory complex (WRC) or disrupt binding to the WRC regulator, Arf1, thereby impairing actin polymerization, synapse formation, and immune cell migration. Diminished cortical actin networks caused by WRC loss led to uncontrolled cytokine release and immune hyperresponsiveness. HEM1 loss also blocked mechanistic target of rapamycin complex 2 (mTORC2)-dependent AKT phosphorylation, T cell proliferation, and selected effector functions, leading to immunodeficiency. Thus, the evolutionarily conserved HEM1 protein simultaneously regulates filamentous actin (F-actin) and mTORC2 signaling to achieve equipoise in immune responses.
Keywords: Actins; ADP-Ribosylation Factor 1; CD4-Positive T-Lymphocytes; Cell Proliferation; Cytokines; Humans; Immunologic Deficiency Syndromes; Lymphoproliferative Disorders; Mechanistic Target of Rapamycin Complex 2; Membrane Proteins; Pedigree; Phosphorylation; Wiskott-Aldrich Syndrome Protein Family

Immunodeficiency, centromeric instability, and facial anomalies (ICF) syndrome with NK dysfunction and EBV-driven malignancy treated with stem cell transplantation. - Burk, Caitlin M; Coffey, Kara E; Mace, Emily M; Bostwick, Bret L; Chinn, Ivan K; Coban-Akdemir, Zeynep H; Jhangiani, Shalini N; Lupski, James R; Ortiz, Damara; Barnum, Jessie L; Allen, Steven W; Robertson, Leanna-Marie; et al. (J Allergy Clin Immunol Pract, 2020)
Keywords: Herpesvirus 4, Human; Humans; Immunologic Deficiency Syndromes; Mutation; Neoplasms; Primary Immunodeficiency Diseases; Stem Cell Transplantation

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Gibbs, Richard A; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin